DETERMINAN NILAI PELANGGAN & IMPLIKASINYA TERHADAP LOYALITAS KONSUMEN DI BANK SYARIAH WILAYAH DKI JAKARTA - Hanan Wihasto; Novi Widiastuti (Program Studi Manajemen, 2019)
The purpose of this study was to determine and analyze the effect of Marketing Communications on Customer Value. To know and analyze the influence of product quality on Customer Value. To know and analyze the influence of Distribution Channels for Customer Value. To know and analyze the effect of Marketing Communications, Product Quality and Distribution Channels together on Customer Value. To know and analyze the impact of the Consumer LoyaltyMarketing Communications. To know and analyze the influence of product quality on Consumer Loyalty. To know and analyze the influence of Distribution Channels for Consumer Loyalty. To know and analyze the effect on the Customer Value Customer Loyalty. To know and analyze the effect of Marketing Communications, Product Quality, Distribution Channels andCustomer Value jointly against Consumer Loyalty. The method used is survey method descriptive and explanatory survey with asample size of 435 respondents, as well as data analysis method used is SEM (Structural Equation Modelling) with LISREL 8.80. Based on the results of the study, then obtained the following findings: Marketing Communications positive and significant impact on Customer Value. Product quality and significant positive effect on Customer Value. Distribution Channels positive and significant impact on Customer Value. Marketing Communication, Product Quality and Distribution Channels simultaneously positive and significant impact on Customer Value. Partially Marketing Communications dominant contribution in influencing the Customer Value. Marketing Communications positive and significant impact on consumer loyalty. Product quality and significant positive effect on consumer loyalty. Distribution Channels positive and significant impact on consumer loyalty. Customer Value positive and significant impact on consumer loyalty. Marketing Communication, Product Quality, Distribution Channels and Customer Value simultaneously positive and significant impact on consumer loyalty. Partially Marketing Communications dominant contribution in influencing consumer loyalty.